2014
DOI: 10.1039/c4an00866a
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric pH sensing using carbon electrodes: glassy carbon behaves similarly to EPPG

Abstract: Developing and building on recent work based on a simple sensor for pH determination using unmodified edge plane pyrolytic graphite (EPPG) electrodes, we present a voltammetric method for pH determination using a bare unmodified glassy carbon (GC) electrode. By exploiting the pH sensitive nature of quinones present on carbon edge-plane like sites within the GC, we show how GC electrodes can be used to measure pH. The electro-reduction of surface quinone groups on the glassy carbon electrode was characterised u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 37 publications
5
61
0
Order By: Relevance
“…It is apparent that the larger window produced the most resolved peaks. The mechanism for the oxidation/reduction reaction of quinones, in buffered solutions, involves a 2e − oxidation that converts the methoxy to the equivalent quinone, followed by a 2e − /2H + exchange to form the hydroxy-quinone [17,18,40]. The potentials at which the redox reactions take place are pH dependent, as the oxidation induces a loss of protons.…”
Section: Optimisation Of the Fbrr-modified Voltammogrammentioning
confidence: 99%
See 1 more Smart Citation
“…It is apparent that the larger window produced the most resolved peaks. The mechanism for the oxidation/reduction reaction of quinones, in buffered solutions, involves a 2e − oxidation that converts the methoxy to the equivalent quinone, followed by a 2e − /2H + exchange to form the hydroxy-quinone [17,18,40]. The potentials at which the redox reactions take place are pH dependent, as the oxidation induces a loss of protons.…”
Section: Optimisation Of the Fbrr-modified Voltammogrammentioning
confidence: 99%
“…Voltammetric pH sensors, which measure the redox potential of a pH dependent moiety, have demonstrated excellent performance in the past [17][18][19], are cost effective and easily miniaturised. The respective redox processes can be quantified using the Nernst equation, yielding the following response at 25°C:…”
Section: Introductionmentioning
confidence: 99%
“…based on the limiting current response of a microelectrode [14] or on dual-plate microtrench electrodes [15]) offer advantages for proton concentration deter-mination at least over limited proton concentration ranges. A new class of "reference-less" pH sensors based on the voltammetric response of pH-dependent surface redox systems has been devel-oped by Compton and coworkers based for example on quinone functionalities grafted onto glassy carbon or graphite surfaces [16][17][18][19][20]. Other types of pH sensor concepts have been proposed, for example a pH-dependent impedance response was reported for aligned single walled carbon nanotubes [21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies of Fe(CN) 6 3-/4-found standard rate constant, k 0 , values at the basal plane ranging from nearly zero (k 0 < 10 -9 cm s -1 ) 31 to little activity (k 0 < 10 -6 cm s -1 ) 22,24 . The hugely enhanced activity at step edges, considered to have a standard rate constant up to 10 7 times higher than the basal surface, was ascribed to the higher local density of electronic states (LDOS) at step edges 24,32 or to catalysis by specific functional groups 33,34 (even for outer-sphere redox couples). These ideas entered textbooks 35,36 and were extrapolated to explain the electrochemical activity of CNTs and graphene.…”
Section: Introductionmentioning
confidence: 99%